2010
DOI: 10.1021/ac100594j
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Differentiation of Seasonal and Pandemic H1N1 Influenza through Proteotyping of Viral Neuraminidase with Mass Spectrometry

Abstract: Signature peptides of the neuraminidase antigen across all common circulating human subtypes of type A and B influenza are identified through the bioinformatic alignment of translated gene sequences. The detection of these peptides within the high-resolution mass spectra of whole antigen, virus, and vaccine digests enables the strains to be rapidly and directly typed and subtyped. Importantly, unique signature peptides for pandemic (H1N1) 2009 influenza are identified and detected that enable pandemic strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…The most prominent bands were detected for nucleoprotein and matrix M1 protein in accord with their higher copy numbers per virion, as evident in our previous studies [18], [19]. The matrix protein constitutes some 40% of the total viral protein while the hemagglutinin and neuraminidase surface antigens constitute only 25% and 5% of all viral protein respectively.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The most prominent bands were detected for nucleoprotein and matrix M1 protein in accord with their higher copy numbers per virion, as evident in our previous studies [18], [19]. The matrix protein constitutes some 40% of the total viral protein while the hemagglutinin and neuraminidase surface antigens constitute only 25% and 5% of all viral protein respectively.…”
Section: Resultssupporting
confidence: 80%
“…It complements related studies that have employed proteomics methods and mass spectrometry to characterise the antigenicity of the influenza virus [15][18]. More recently, it has been shown that the proteotyping approach can distinguish seasonal from pandemic type A H1N1 influenza strains [19] and also assign the lineage of human strains of type A H1N1 and type B influenza virus [20].…”
Section: Introductionmentioning
confidence: 80%
“…Solutions of viral peptides (1 l) were diluted with a solution (4 l) of matrix (5 mg/ml ␣-cyano-4-hydroxycinnaminic acid in 50% acetonitrile with 0.1% trifluoroacetic acid), and 1 l was spotted onto a matrix-assisted laser desorption ionization-Fourier-transform ion cyclotron resonance (MALDI-FT-ICR) mass spectrometry sample plate (MTP AnchorChip 400/384 TF; Bruker Daltonics, Billerica, MA). MALDI-FT-ICR mass spectra were recorded with a 7T Bruker APEX-Qe instrument (Bruker Daltonics, Billerica, MA) in the positive-ion mode, as described previously (8)(9)(10)(11). The mass spectra shown are representative of mass spectra obtained from three replicate experiments.…”
Section: Growth Of Clinical Virus Specimensmentioning
confidence: 99%
“…The approach has been shown to be able to distinguish seasonal and pandemic influenza strains (10), to determine strain lineages (11), and to identify reassortant viruses that pose the greatest pandemic risk (12). The practicality of this proteotyping approach for the surveillance of circulating strains of the virus, in terms of primary clinical specimens grown in cell culture, is demonstrated here for the first time.…”
mentioning
confidence: 97%
“…The high-resolution MS of whole antigen, virus or vaccine digests allows a rapid subtyping of influenza strains using the neuraminidase as marker. Even, the pandemic (H1N1) 2009 influenza strain has an unique signature peptides different from seasonal type A (H1N1) influenza strains [151].…”
Section: Virus Strain Typingmentioning
confidence: 99%